Feasibility Study for Development of Baros Fish Laboratory, in Serang Regency - Forcep Rio Indaryanto (JURNAL PERIKANAN DAN KELAUTAN, 2011)
A strong demand for high quality of fish seeds can not be fulfilled by the production of seed in the area of Serang district. Many people have to fulfill their needs from out side Banten area. Therefore, in order to support in solving the problem, the Office of Marine and Fisheries Servise of Serang District Government through their laboratory of fish breeding (BBI) in Baros Serang, proposing the development of breeding facilities to enlarge the increasing demand of high quality of fish seeds. This program is important to support the developmen in fish culture in Serang district as well as in Banten Province. A feasibility study for the development of the laboratory of fish breeding have been done on December 1 to 30 March 2011 with using qualitative descriptive analysis method, a simple quantitative analysis and measurement of water quality. Location of the BBI Baros was very suitable, However, the land Area of BBI is inadequate to operate in large scale production. Accordingly, in implementing fish farming based on Indonesian National Standard (SNI), Ways of Good Fish Hatchery (CPIB), Fish Ways Good (CBIB) and stem and seed certification requires Laboratory facilities are adequate. The optimal areas for fish breeding laboratory is about 4 hectares, to prepare the large production scale.